Biochar co-compost increases the productivity of Brassica napus by improving antioxidant activities and soil health and reducing lead uptake - Jiang, Wenjie; Liu, Ying; Zhou, Jing; Tang, Haiying; Meng, Guiyuan; Tang, Xianrui; Ma, Yulong; Yi, Tuyue; Gad Elsaid, Fahmy (Frontiers in Plant Science, 2024)
is a serious toxic metal without any beneficial role in biological system. Biochar (BC) has emerged as is an excellent soil amendment to mitigate the the toxicity of heavy metals (HMs).Pb toxicity. Nevertheless, tThe impact of BC co-compost (BCC) in mitigating the toxic impacts of Pb has not been studied yet. Therefore, this study aimed to evaluate the potential of BC and BCC in improving Brassica growth, physiological and biochemical traits of Brassica nupus, soil properties and reducing health risks (HR). The study was comprised of following treatments:different Pb concentrations (control and Pb stress (100 mg kg -1 ) and organic amendements (control, BC, compost, and BCC). Results indicated that Pb stress reduced the growth, photosynthetic pigments, grain seed yield, and oil contents by increasing hydrogen peroxide (H2O2) production, Pb uptake and accumulation in plant tissues and decreasing photosynthetic pigments and nutrients availability. , and increased antioxidant activities, tissue Pb concentration, and health risks. However, The application of BCC alleviated the the adverse impacts of Pb and improved grain seed production (40.24%), and oil yield (11.06%) by increasing chlorophyll a (43.18%), chlorophyll b (25.58%) synthesis, relative water content (23.89%), total soluble protein (TSP: 23.14%), free amino acids (FAA: 26.47%), proline (30.98%), APX (40.90%), CAT (32.79%), POD (24.93%) and SOD (33.30%) activity. Biochar co-compost mediated increase in seed and oil yield was also linked with also reduced the accumulation of Pb in plant parts, (root, shoot, and grain) and soil Pb availability and improved the soil-available phosphorus, potassium, total nitrogen, soil organic carbon (SOC), and microbial biomass carbon (MBC), resulting in better plant performance. Moreover, Further, BCC also reduced the bioaccumulation concentration, daily metal intake, hazard index, and target hazard quotient. Therefore, the In conclusion application of BCC can increased growth, yield, and oil contents of Brassica napus by improving physiological and biochemical traits, osmolytes accumulation, antioxidant activities, soil properties, and reducing the Pb uptake.